Sports Performance Analysis of Wheelchair Basketball Players Considering Functional Classification - Víctor Hernández-Beltrán; Luis Felipe Castelli Correia de Campos; Mário C. Espada; José M. Gamonales (Applied Sciences, 2024)
Wheelchair basketball (WB) is a sport modality adapted for people with disabilities who present functional classification (FC) according to their mobility, from 1.0 for players with lesser functional capacity up to 4.5 for great mobility and trunk control players. This study aimed to analyze and compare the external load (EL) and the internal load (IL) of the WB players according to their FC in 5 × 5 simulation game tasks. The main objective of this task was to develop a simulated game in which two teams of five players faced each other to resemble the physical demands of an official match. The development of these tasks allowed for the players to learn the different systems of play, and to improve tactical skills. To conduct the study, 12 (male) national professional WB players (years: 30.7 ± 4.82 and WB experience: 5 ± 1.43) participated in the study and were grouped according to FC. WIMU PROTM devices monitored the EL manufactured by RealTrack Systems in Almería, Spain, and to measure the player’s IL, GarminTM Heart Rate (HR) bands were used (GarminTM in Olathe, KS, USA). The EL variables were divided as kinematic (distance, explosive distance, acc, dec, max. acc, max. dec, average speed, max. speed) and neuromuscular (player load, impact). The IL variables were average HR, max. HR and %max. HR. The main results show that players with greater functional capacity (FC = 4.0) developed higher values in the IL and neuromuscular variables analyzed (p < 0.05), as well as in some kinematic variables like distance, dec and average speed (p < 0.05). This information is relevant because it helps to personalize the training load based on competitive demands and create a gradual and adaptable training program. This information helps athletes to develop better performance during training and prevent injuries caused by overexertion.